Numerical modelling of tide-surge interaction and its influence in estuarine inundation patterns - Pinheiro, João Pedro Santos (2018)
Several problems related with coastal flooding depend on tidal properties and on sea level rise induced by meteorological effects (storm surge). The water levels during storms are consequently determined by tidal and storm surge levels as well as by their non-linear interaction. Herein, shallow coastal systems are particularly important, since the local bathymetry is a crucial mechanism controlling the interaction between tide and storm surge. Thus, the main concern of this dissertation is to give new insights about the effect of tide-surge interaction on the inundation patterns of a flood prone shallow estuarine system located in the northwest Portuguese coast, the Ria de Aveiro. The methodology adopted comprised two fundamental steps: 1) statistical analysis of sea level data collected at the lagoon inlet between 1979 and 2013, in order to infer about the frequency distributions of positive residual events and their relation with tidal phase; 2) implementation, calibration, validation and exploitation of a numerical application based on Delft3D hydrodynamic model, in order to describe the local estuarine circulation (including the marginal areas potentially flooded during adverse conditions), and explore inundation conditions and tidesurge interactions under the scenarios arising from the previous task. The statistical analysis revealed that the frequency distributions do not depend on the threshold used, as well as on the minimum number of hours to an event be assigned. The results highlighted a tendency for storm surge events to occur most frequently on the falling tide, with a principal mode of occurrence 3 hours after high water. Besides that, the highest storm surge peaks have occurred at the beginning of rising tide and at the end of falling tide. The numerical model results evidence that the model is able to reproduce tidal and storm surge propagation more accurately than previous numerical applications developed for Ria de Aveiro. Once calibrated the model, a set of numerical experiments (hypothetical scenarios) were designed to assess the effect of tide on storm surge propagation along Ria de Aveiro and its influence in local inundation patterns. Thus, it was found that storm surge characteristics are modulated by the state of the tide, where the effect of nonlinear terms is to reduce the storm tide peak. However, at the upper reaches of the main channels the storm tide peak is controlled by the storm surge, since it is higher than tide. Concerning to the lagoon flooded area, the different scenarios showed that the most threatened areas are the upper reaches of São Jacinto channel and the vicinity of Laranjo bay, resulting this from the increase of storm tide peak in these regions. The adjacent margins of Baixo Vouga Lagunar and the margins of Mira/Ílhavo channel are also threatened when the tidal range is increased. This results from an increase on nonlinear tide-surge interaction and also on the maximal residual levels.